PENERAPAN MEDIA PEMBELAJARAN LUMIO BY SMART UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI PERUBAHAN SOSIAL KELAS IX-D SMPN 18 SURABAYA TAHUN PELAJARAN 2024-2025 - Andayani, Yuyun Astri; Rindawati; Ririn Fatayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The learning outcomes of Class IX D students on the topic of social change at SMPN 18 Surabaya are still low. This study aims to improve student learning outcomes on this topic by implementing Lumio by Smart as a learning medium. This research is a classroom action study conducted in three stages: pre-cycle, the first cycle, and the second cycle. Each cycle includes several key steps: planning, implementation, observation, and reflection. The subjects of the study consisted of 32 students from Class IX D in the 2024-2025 academic year. According to the research results, before the implementation of Lumio by Smart, only 10 students, or approximately 31.25%, achieved the Learning Objective Mastery Criteria (KKTP). However, after the implementation of this learning medium, there was a significant improvement. In the first cycle, the number of students achieving KKTP increased to 23 students, or 71.87%. Furthermore, in the second cycle, the number increased to 28 students, or 87.50%. Therefore, it can be concluded that the implementation of Lumio by Smart can improve student learning outcomes, especially in the topic of social change.